EL PENSAMIENTO EN LA CLASE DE INGLÉS: FUENTE DE PODER O VULNERABILIDAD - Rubio Alcalá, Fernando D. (ELIA: Estudios de Lingüística Inglesa Aplicada, 2017)
Abstract The students’ thoughts are a source of power when they are used correctly in the EFL classroom, but, on the contrary, they may be an obstacle to learning and cause emotional instability if the students do not use them well. According to general studies of psychology, thoughts can be classified as relevant and irrelevant. A relevant thought takes place when a person dedicates his thinking to a specific task. For instance, a student is doing a multiple-choice exercise about phrasal verbs, and makes hypothesis and deductions from his knowledge of phrasal verbs in order to do the exercise. Then, as those relevant thoughts take place, other thoughts that are not related directly to that exercise emerge. Those can be irrelevant thoughts when they do not help in doing the task, and interfere with relevant thoughts. They refer to intrapersonal matters, as self-efficacy, motivation, self-esteem, etc. For instance, the student thinks: “I won’t be able to do the exercise” or “I should have studied harder”, etc. However, these irrelevant thoughts can be facilitating to the task if the student is able to analyze those thoughts and change them into positive ones: “I will do my best” or “Although I have not studied hard, I will give it a chance” .This paper shows how cognition and emotion relate to each other and how relevant and irrelevant thoughts are created. It will also explain how the language learner employs self-defense mechanisms as s/he finds difficulties or aversion in doing learning tasks. As a general consideration, irrelevant thoughts can be as important as relevant thoughts in learning a language. Moreover, many researchers claim that they are responsible for determining success or failure in ordinary classroom learning tasks.